Opening address by the President - O'Connor, R. (Statistical and Social Inquiry Society of Ireland, 1983)
Since its formation in 1847 the Statistical and Social Inquiry Society has always provided a forum for discussion of the more important economic and social policy issues facing the country. Throughout its long history, the Society has always sought papers on the more topical issues and this procedure has continued to the present time. Indeed, governments now expect that green and white papers, as well as important reports, will be discussed by the Statistical Society, so that in formulating policy they will have before them informed opinions on the issues involved and on the problems which certain proposals may bring about.
Symposium on Industrial Policy in Ireland
Read before the Society, 2 December 1982
Keywords: Irish industrial policy; Statistical and Social Inquiry Society of Ireland; Irish Development Authority; Industrial development; 314.15